Diana Sacayán case: Femicide or travesticide? - Infante, Nora Alicia (2022)
This paper analyzes transvesticide as a gender crime, as well as the responsibility of the State in the violation of the rights of transvestite femininities. It also reviews one of the emblematic cases of death in the transvestite collective, that of Diana Sacayán, which in a historical event was called "transvesticide" by the judges of the Criminal Oral Trial Court No. 4, that is, the result of a continuum of violence that especially affects transvestites.